Problematika Konseptual Materi Muzakkar dan Muannast dalam Pembelajaran Bahasa Arab - Muhammad Solihin Pranoto; Heni Dwi Rahayu; Laudya Sintia Putri (CV. Jalan Cendikia, 2026)
This research provides a comprehensive analysis of the conceptual barriers encountered by Arabic learners in mastering gender categories, specifically Muzakkar and Muannas. Within Arabic grammar, gender classification serves as a crucial structural foundation influencing syntactic integrity, yet for non-native speakers, it often triggers ambiguities that impede overall proficiency. Employing a library research method with content analysis, this study examines classical Nahwu literature and contemporary journals to map linguistic problem patterns. The findings highlight three fundamental constraints: first, the perceptual conflict between universal biological gender and arbitrary linguistic gender which lacks equivalence in the learners' native languages; second, morphological inconsistencies regarding feminine markers, particularly the specific sima’i vocabulary that lacks visual cues and misleads learner logic; and third, the complexity of mutabaqah rules requiring strict gender agreement across complex sentence components. The study concludes that instruction must shift from rigid rote memorization toward an applied, contextual pedagogical approach. It is recommended that educators systematically map anomalous words to facilitate a smoother cognitive transition for students. These findings offer a significant theoretical contribution to developing systematic Arabic modules designed to minimize linguistic obstacles and enhance the learning process through more structured, highly adaptive, and ultimately more effective teaching methodologies for all students globally.